Studies on colonisation of fly ash disposal sites using invasive species and aromatic grasses - Maiti, Deblina; Prasad, Bably (Journal of Environmental Engineering and Landscape Management, 2017)
Fly ash disposal activities by coal based thermal power plants will continue to be a serious issue across the globe due to its hiked generation every year. To obviate the hazardous effects of fly ash disposal sites on the surrounding ecosystems, rapid stabilization of the dumps is essential. This paper conglomerates the past activities, challenges; present scenario of vegetation establishment on these sites as well as future research requirements based on various experimental case studies. An insight has been presented on the usefulness of native, tuft, aromatic grasses which can reduce the length of successive phases in reclamation programmes and also enhance the fertility of the substrate as found from the significantly increased nitrogen content in the present field sites. Metal bioaccumulation studies depicted that by virtue of high biomass production potential of Saccharum spontaneum it can also be used as a phytoextractor of toxic metals, thus helping in phytoremediation of the metals in fly ash. Field studies allude the fact that knowledge of phytodiversity of old fly ash deposits is essential for a right choice of species before every reclamation programme. Secondly, application of amendments is conjointly a prerequisite for establishment of plants on fly ash. In a pot scale study it was found that lower rate of amendment application (2–5% farmyard manure and 5–10% topsoil on weight basis) in fly ash improves the growth and biomass of Cymbopogon citratus. Extensive root system of the grass was substantiated by high root: shoot biomass which stabilized the surface of the ash. To investigate the possibilities of ground water contamination due to amendments leaching studies were carried out.  An initial high concentration of some ions marginally near permissible limit as per Indian drinking water standards was observed but their concentrations were below acceptable limit during harvestable stages. Above studies can contribute significantly in field studies through a properly planned restoration programme.